The books of Nahum, Habakkuk, and Zephaniah - Renz, Thomas (New International Commentary on the Old Testament (NICOT), 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Excursuses -- General Editor's Preface -- Author's Preface -- Abbreviations -- Select Bibliography -- Introduction to Nahum, Habakkuk, and Zephaniah -- I. The Nature of Prophetic Books -- II. The Minor Prophets in the Canon -- III. The Unity of the Book of the Twelve -- IV. Nahum, Habakkuk, and Zephaniah in the Book of the Twelve -- V. Nahum, Habakkuk, and Zephaniah and Their Constituent Units -- VI. An Outline of the Late Neo-assyrian and Early Neo-babylonian Period -- The Book of Nahum -- Introduction -- I. The Profile of the Book -- A. The Superscription -- B. Macrostructure -- C. Language and Style -- D. Textual Witnesses -- II. The Development of the Book -- A. General Comments on the Origin of the Book -- B. The Individual Units within the Book -- C. The Redaction of the Book of the Twelve -- III. The Rhetorical Function of the Book -- A. The Message of Nahum's Poetry at the Time of Its Origin -- B. Nahum's Place in the Book of the Twelve -- C. Nahum's Place in the Biblical Canon -- D. Nahum in the History of Interpretation -- E. Nahum's Place in the Church Today -- Text and Commentary -- I. The Superscription to the Book (1:1) -- II. Contemplating Yhwh, the Avenging God (1:2-10) -- III. Accusation against the City (1:11) -- IV. Yhwh's Verdict (1:12-14) -- V. Announcement of Deliverance (1:15 [2:1]) -- VI. Images of the Fall of Nineveh (2:1-10[2-11]) -- VII. Ridicule of the King of Nineveh (2:11-12[12-13]) -- VIII. Prophecy of Complete Destruction (2:13[14]) -- IX. Doom and Humiliation for the Bloodflow City (3:1-7) -- X. Denunciation of the City's Complacency (3:8-12) -- XI. Exposition of the Uselessness of the City's Defenses (3:13-17) -- XII. Exposition of the Helplessness of the City's Ruler (3:18-19) -- The Book of Habakkuk -- Introduction.